Strategies For Managing Objects and Natural Attractions in Semongkat Natural Tourism Park, Batulanteh District, Sumbawa Regency - Rusli Duby; Endah Wahyuningsih; Hairil Anwar (Jurnal sosial dan sains, 2022)
This research aims to find out the feasibility of Semongkat Natural Tourism Park as an object and natural tourist attraction and menemukenali natural tourism park management strategy semongkat. This research uses quantitative and qualitative methods. Population in this study is divided into several groups, namely the semongkat natural tourism park management group, the semongkat hamlet community group and the semongkat natural tourism park visitor group. Determination of respondents for semongkat natural tourism park managers using purposive sampling methods. After the respondent is considered to understand then the determination of respondents in this study is based on snowball sampling techniques which is one form of judgment sampling. Data collection techniques use literature studies, interviews, observations, and questionnaires. The data analysis used in this study is the Guidelines for Analysis of The Area of Operations and Natural Attractions (ADO-ODTWA) of the Director General of PHKA 2003 and SWOT analysis. From the analysis of the data, it shows that Semongkat Natural Tourism Park deserves to be developed with a feasibility presentation of 76.11% can be done using the SO (Strenght-Opportunity) strategy, namely developing tourist attractions and all tourism potential contained in semongkat natural tourism parks.